Low level of stroke care awareness among stroke patients’ caregivers: an important but neglected area of stroke care - Sharma, N; Sharma, M; Lopchan, M; Thapa, L; Rana, PVS (Journal of College of Medical Sciences-Nepal, 2014)
Objective Stroke is one of the leading causes of mortality and morbidity worldwide. Stroke patients require longterm care for better outcome. Most often family members are the back bone of the service provided to people affected by stroke. Stroke patients and their caregivers are known to have large gaps in stroke knowledge and have suboptimal personal health behaviors, thereby putting the patient at high risk for complications. Our study was designed to explore the stroke care awareness among stroke patients' caregivers. Methods 50 stroke caregivers aged >18 years from neurology ward of College of Medical Sciences-Teaching Hospital were selected by non-probability purposive sampling from June 2012 to July 2012. Questionnaire focusing basic stroke care was prepared by researchers with the help of literature and a neurophysician. Validity and reliability of the tools were tested and data collected. Analysis of collected data was done using SPSS 16.0. Results The mean age of the respondents was 40 years (range: 20-80 years). Thirty-nine (78%) were either spouse or children. Thirty-eight (76%) caregivers were literate. Overall, 27 (54%) caregivers had low level of awareness regarding stroke care and mean knowledge score was 23.7. Conclusion This study has revealed the existence of low level of stroke care awareness amongst stroke caregivers. Interventional education program oriented to address this important yet neglected area can improve the stroke care in countries like Nepal where recent advancement for stroke management is lacking. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-3, 1-8